2021
DOI: 10.1039/d1py00988e
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular dendrimer-containing layer-by-layer nanoassemblies for bioapplications: current status and future prospects

Abstract: Dendrimers are powerful synthetic macromolecular architectures for a wide variety of bioapplications owing to their unique and superior features, including monodispersity, well-defined and highly branched architecture, multivalency, tunable size and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 242 publications
0
6
0
Order By: Relevance
“…The current mainstream of functional material fabrication is a combination of basic technologies such as organic synthesis, self-assembly, or structure fabrication methods such as the Langmuir-Blodgett (LB) method [130,131] or layer-by-layer (LbL) assembly [132][133][134]. These conventional methodologies are now being used to create materials that can address social issues such as energy requirements [135,136], the environment [137,138], and medicine [139,140]. Many analytical studies have shown that high effectiveness and activity are due to features at the atomic and molecular level [141,142].…”
Section: Perspectivesmentioning
confidence: 99%
“…The current mainstream of functional material fabrication is a combination of basic technologies such as organic synthesis, self-assembly, or structure fabrication methods such as the Langmuir-Blodgett (LB) method [130,131] or layer-by-layer (LbL) assembly [132][133][134]. These conventional methodologies are now being used to create materials that can address social issues such as energy requirements [135,136], the environment [137,138], and medicine [139,140]. Many analytical studies have shown that high effectiveness and activity are due to features at the atomic and molecular level [141,142].…”
Section: Perspectivesmentioning
confidence: 99%
“…Electrostatic interactions have been widely applied in the fabrication of nanoassemblies utilizing charged components [ 125 , 126 ]. Many first-line PDT PSs (e.g., Rose Bengal, Ce6, and protoporphyrin) are negatively charged with high singlet-oxygen generation efficiency [ 118 , 119 , 127 ].…”
Section: Photosensitizers Utilized With Hyperbranched Polymersmentioning
confidence: 99%
“…Electrostatic interactions have been widely applied in the fabrication of nanoassemblies utilizing charged components [125,126]. Many first-line PDT PSs (e.g., Rose Bengal, Ce6, and protoporphyrin) are negatively charged with high singlet-oxygen generation As discussed in previous sections, HB polyglycerols possess good biocompatibility and long blood circulation times, and they are good candidates as PS carriers for PDT applications.…”
Section: Photosensitizers Encapsulated In Hyperbranched Polymersmentioning
confidence: 99%
“…23,24 The aforementioned unique structural properties of dendrimers make them promising candidates for potential application in biomedicine, drug delivery, diagnostics, catalysis, supramolecular materials, etc. [25][26][27][28][29][30][31] As a unique type of molecular-scale building block, dendritic molecules have been widely utilized in the construction of supramolecular gel materials in the last two decades. [32][33][34][35] In contrast to traditional LMWGs, the dendritic branching architecture ensures that there are multiple recognition sites for formation of intermolecular non-covalent interactions, which is beneficial to form robust gel-phase materials due to the multivalent effect.…”
Section: Zhi-xiong Liumentioning
confidence: 99%